Anti-leishmanial activity of 29 daily sessions of intralesional-pentavalent antimony administration on Leishmania (Viannia)-infected BALB/c mice - Vera, Angélica María (2021)
Introduction: Intralesional-pentavalent antimonials (IL-SbV) are recommended for simple cutaneous leishmaniasis (CL). Few treatment sessions (1-5) and drug volumes (1-5 ml each), relative to lesion size (LS), are recommended. There is not a validated IL-SbV protocol using doses calculated as mg/kg body weight and administered over a large number of IL-sessions, with small injection volumes. Objective: The study aim was to determine the efficacy of different concentrations of IL-SbV administered in 29 daily sessions of 100 μL each, on CL infected mice. Methods: Leishmania (Viannia) panamensis and L. (V.) braziliensis-infected mice (N = 6) were treated with 150, 50, and 16.6 mgSbV/kg/day x 29 days. Percentage of lesion area reduction, aesthetic and final (no lesions, no parasites) efficacy and effective dose (ED)50 were determined. In vitro-SbV activity against parasites was evaluated for both species. Results: The ED50 values were 72.2 and 66.3 (at the end of treatment), 54.3 and 37.7 (15-days pt.), and 145.3 and 148.6 (60-days pt.) for each species, respectively. Differences were observed between Leishmania species at 15-days pt., but not later. At 60-day pt., IL-SbV-150 mg showed final cure rates of 66.6 % for L. (V.) panamensis and 33.3 % for L. (V.) braziliensis-infected mice. After 15 days pt., lesion reactivation was observed in some “aesthetically cured” mice. Glucantime was not active in in vitro assays. Conclusions: The IL-SbV use with a dose calculated as mg/kg body weight and administered over a large number of IL-sessions, with small injection volumes each day could be effective against L. (V.) panamensis and L. (V.) braziliensis-CL infection. An appropriate SbV-dose (higher than 150 mg/kg/day x less than 29 days) must be evaluated.